Oral Janus kinase inhibitors for maintenance of remission in ulcerative colitis - Davies, Sarah C (Cochrane Database Syst Rev, 2020)
BACKGROUND: Tofacitinib is an oral Janus kinase (JAK) inhibitor which blocks cytokine signaling involved in the pathogenesis of autoimmune diseases including ulcerative colitis (UC). The etiology of UC is poorly understood, however research suggests the development and progression of the disease is due to a dysregulated immune response leading to inflammation of the colonic mucosa in genetically predisposed individuals. Additional medications are currently required since some patients do not respond to the available medications and some medications are associated with serious adverse events (SAEs). JAK inhibitors have been widely studied in diseases including rheumatoid arthritis and Crohn's disease and may represent a promising and novel therapeutic option for the treatment of UC. OBJECTIVES: The primary objective was to assess the efficacy and safety of oral JAK inhibitors for the maintenance of remission in participants with quiescent UC. SEARCH METHODS: We searched the following databases from inception to 20 September 2019: MEDLINE, Embase, CENTRAL, and the Cochrane IBD Group Specialized Register, WHO trials registry and clinicaltrials.gov. References and conference abstracts were searched to identify additional studies. SELECTION CRITERIA: Randomized control trial (RCTs) in which an oral JAK inhibitor was compared with placebo or active comparator in the treatment of quiescent UC were eligible for inclusion. DATA COLLECTION AND ANALYSIS: Two review authors independently screened studies for inclusion and extraction. Bias was assessed using the Cochrane 'Risk of bias' tool. The primary outcome was the proportion of participants who failed to maintain remission as defined by any included studies. Secondary outcomes included failure to maintain clinical response, failure to maintain endoscopic remission, failure to maintain endoscopic response, disease‐specific quality of life, adverse events (AEs), withdrawal due to AEs and SAEs. We calculated the risk ratio (RR) and 95% confidence intervals (95% CI) for each dichotomous outcome. Data were analyzed on an intention‐to‐treat basis. The overall certainty of the evidence supporting the outcomes was evaluated using the GRADE criteria. MAIN RESULTS: One RCT (593 participants) including patients with moderately to severely active UC met the inclusion criteria. Patients who achieved a clinical response after eight weeks of induction treatment with tofacitinib (10 mg twice daily) or placebo were randomly assigned in a 1:1:1 ratio to receive maintenance therapy with tofacitinib at 5 mg twice daily, 10 mg twice daily or placebo for 52 weeks. The primary endpoint was remission at 52 weeks and the secondary endpoints included mucosal healing at 52 weeks, sustained remission at 24 and 52 weeks and glucocorticosteroid‐free remission. This study was rated as low risk of bias. The study did not report on the proportion of participants who maintained remission at 52 weeks as clinical remission was not required for study entry (just clinical response). Thus we report on the proportion of participants who achieved clinical remission, clinical response, and endoscopic remission at 52 weeks; the proportion of participants who maintained remission at 52 weeks, and on AEs, SAEs and withdrawal due to AEs. However, the included study did not report on endoscopic response or disease‐specific quality of life. Sixty‐three per cent (247/395) of tofacitinib participants failed to achieve clinical remission at 52 weeks compared to 89% (176/198) of placebo participants (RR 0.70, 95% CI 0.64 to 0.77; high‐certainty evidence). The number needed to treat for an additional beneficial outcome is 4. Forty‐three per cent (171/395) of tofacitinib participants failed to maintain clinical response at 52 weeks compared to 80% (158/198) of placebo participants (RR 0.54, 95% CI 0.48 to 0.62; high‐certainty evidence). Eighty‐four per cent (333/395) of tofacitinib participants failed to achieve endoscopic remission at 52 weeks compared to 96% (190/198) of placebo participants (RR 0.88, 95% CI 0.83 to 0.92; high‐certainty evidence). AEs were reported in 76% (299/394) of tofacitinib participants compared with 75% (149/198) of placebo participants (RR 1.01, 95% CI 0.92 to 1.11; high‐certainty evidence). Commonly reported AEs included worsening UC, nasopharyngitis, arthralgia (joint pain)and headache. SAEs were reported in 5% (21/394) of tofacitinib participants compared with 7% (13/198) of placebo participants (RR 0.81, 95% CI 0.42 to 1.59; low‐certainty evidence). SAEs included non‐melanoma skin cancers, cardiovascular events, cancer other than non‐melanoma skin cancer, Bowen's disease, skin papilloma and uterine leiomyoma (a tumour in the uterus). There was a higher proportion of participants who withdrew due to an AE in the placebo group compared to the tofacitinib group. Nine per cent (37/394) of participants taking tofacitinib withdrew due to an AE compared to 19% (37/198) of participants taking placebo (RR 0.50, 95% CI 0.33 to 0.77; moderate‐certainty evidence). The most common reason for withdrawal due to an AE was worsening UC. The included study did not report on endoscopic response or on mean disease‐specific quality of life scores. AUTHORS' CONCLUSIONS: High‐certainty evidence suggests that tofacitinib is superior to placebo for induction of clinical and endoscopic remission at 52 weeks in participants with moderate‐to‐severe UC who had a clinical response after eight weeks of induction treatment with tofacitinib (10 mg twice daily) or placebo. The optimal dose of tofacitinib for maintenance therapy is unknown. High‐certainty evidence suggests that there is no increased risk of AEs with tofacitinib compared to placebo. However, we are uncertain about the effect of tofacitinib on SAEs due to the low number of events. Further studies are required to look at the long‐term effectiveness and safety of using tofacitinib and other oral JAK inhibitors as maintenance therapy in participants with moderate‐to‐severe UC in remission.